The Revolution of Brick-and-Mortar-Retail - Pop-up Stores – a Taxonomy - Sophie Schüller; Bianca Viola Jud (Marketing Review St.Gallen, 2018)
In recent years, the phenomena pop-up store has been spreading all over the world. Numerous reasons have compelled various companies from different industries to adopt this new retail format. Just as versatile are the strategic objectives and forms of appearances of pop-up stores. This article, therefore, aims to identify different pop-up store types and to categorize them according to their applicability.
Keywords: 650